Penggunaan Pendekatan Kontekstual untuk Meningkatkan Hasil Belajar Bahasa Indonesia Materi Pelajaran Menulis Puisi di Madrasah Ibtidaiyah Negeri Selat Hulu Kapuas - Khairunnisa, Khairunnisa (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2014)
In teaching writing, contextual learning means learning to unleash the full potential of a student naturally. Students are given the opportunity to apply and develop ideas critically and communicative in the form of written language which can be meaningful for themselves and for those who read it. This thesis aims are: 1) To know the differences in the learning result of Indonesian subject in poetry writing material among the students who learn with contextual approach and the students who learn with conventional approach, and 2) To know the effectiveness of using contextual approach in improving the learning result of Indonesian subject on poetry writing material. This research used a quasi-experimental design. The subject was the fifth grade students of MIN Selat Hulu Kapuas academic year 2012/2013. Class Va as experimental group and class Vb as control group. The taught material is writing poetry. The first data of students’ ability is taken from pretest result, while the posttest result is used as research data. The results showed that there are significant differences between the students’ learning results of Indonesian subject in experimental group with control group. If seen from the average value of the posttest, the results of learning in the experimental group (75.87) is higher than the average value of the control group (68.13). This difference was also confirmed by the results of the calculations of Independent-sample T-Test which significance value is smaller than the sig. = 0.05 which is equal to 0.002. This showed that the use of the contextual approach can improve students’ learning result. Meanwhile, the effectiveness test calculations showed that the average value of g factor in the experimental group showed 0.49 points. This means, the use of a contextual approach in Indonesian subjects is quite effective in improving student learning result in the subject matter writing poetry.